3D printing: Balancing innovation for sustainability with emerging environmental and health risks - Andi Alijagic; Damir Suljevic; Magnus Engwall; Eva Särndahl (iScience)
Summary: The rapid rise of 3D printing, both in industrial and home settings, presents emerging health and environmental risks. While 3D printing enhances sustainability by reducing waste and optimizing resource use, its impact on human health remains poorly understood. The use of metals and polymers linked to health risks, coupled with the release of inhalable particles and volatile organic compounds, raises concerns about respiratory and systemic effects. The absence of clear guidelines creates high public demand for information and limits safe implementation, particularly in schools and homes where millions of 3D printers are expected by 2030. Additionally, improper disposal of 3D printing polymer materials may exacerbate plastic pollution. This article proposes the perspective of a structured risk assessment framework set on particle emissions from industrial 3D printing. It will offer a practical tool to bridge current knowledge gaps and to inform safe practice and policy development, because immediate action is necessary to balance innovation with safety.